Rule of Law and Human Rights Challenges in South East Asia: A Case Study of Legal Pluralism in Indonesia - Isra, Saldi; Ferdi, Ferdi; Tegnan, Hilaire (Hasanuddin Law Review, 2017)
It has been over 72 years since Indonesia proclaimed her independence on 17 August 1945. However, the 350 years of the Dutch colonization is still impacting the lives of the Indonesian people. The difficulties faced by the Indonesian legal system as the government tries to accommodate adat (custom) and religion principles within the national law and the extent to which this legal mechanism affects the everyday life of the Indonesian people. In a nation where customs and religion are so preeminent, setting up an all-inclusive document meant to be the foundation of the stateâs legal system at the dawn of independence was no easy task. This paper discusses the practice of legal pluralism in Indonesia and its struggle to implement rule of law and human rights principles after a half-century of authoritarian regimes. The study involves socio-legal research drawing on empirical data. Survey research was conducted between September 2014 and February 2015 at Utrecht University, the Netherlands, as well as in 5 cities in Indonesia (Aceh, Bali, Batam, Medan, and Padang) to collect data. The research reveals that legal pluralism is not helping to strengthen the Indonesian legal system, and that the foreignness of the Western law along with the neglect of the Indonesian customary and Islamic laws, totalitarianism and military involvement in politics, corruption within the state apparatus and unsynchronized laws weaken the legal system in Indonesia and hinder its effort to implement rule of law and human rights principles.